Examine the Role of Brand Experience in Value Co-creation. - Khachontantiphop, Phalida (2011)
The previous experience with brand influences the consumer decision and consumer behavior. The brand is significant criteria in the evaluation of brand alternatives, especially co-creation of value. The co-creation offering is able to assess when the consumer participate and consume it. The consumer has the difficulty to make the purchasing decision. Moreover, the co-creation requires the higher involvement from the consumer to participate in the co-creation process with the company. The brand is beneficial for consumer to make the decision in co-creation. The research aims to examine the role of brand experience in value co-creation. The research studies in the specific context of self-cooking restaurant in Thailand. The self-cooking restaurant uses for the representation of co-creation of value. Thai people are familiar with the self-cooking restaurant that distributed intensively. Self-cooking in Thailand allows the consumer to participate in the production process. The consumer participates and co-created the foods in the production process with the company. The consumers have the opportunity to select the wide range of prepared ingredients in the menu list. The dimension of brand experience was constructed by Brakus, Schmitt and Zarantonello (2009) which combined four dimensions: sensory, affective, intellectual and behavioral. The research in the specific content of self-cooking restaurant in Thailand asserted the four dimensions similarly to the previous research. The research in the co-creation case generated the relevant information with another dimension, social dimension. The consumer valued and responded to the experience with brand in the social aspect. The social dimension was considered as the significant dimension of brand experience in the co-creation case.